2012
DOI: 10.1007/s10695-012-9676-3
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L in the orange-spotted grouper, Epinephelus coioides: molecular cloning and gene expression after a Vibrio anguillarum challenge

Abstract: The orange-spotted grouper, Epinephelus coioides, is an important fish maricultured in many Asian countries. In the present study, the full-length cDNA of cathepsin L, an immunity related gene of fishes, was isolated from E. coioides using rapid amplification of cDNA ends (RACE). It is 1,443 bp in length, including an open reading frame (ORF) of 1,011 bp. The open reading frame encoded a preproprotein of 336 amino acids (aa), which consisted of a signal peptide of 16 aa, a proregion peptide of 98 aa and a matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In this respect, the knowledge on molecular and genetic mechanisms of fish resistance to these pathogens, as well as on the features of the induced immune response, should greatly benefit the development of efficient control strategies (Chistiakov et al, 2007;Caipang et al, 2008;Liang et al, 2012).…”
mentioning
confidence: 99%
“…In this respect, the knowledge on molecular and genetic mechanisms of fish resistance to these pathogens, as well as on the features of the induced immune response, should greatly benefit the development of efficient control strategies (Chistiakov et al, 2007;Caipang et al, 2008;Liang et al, 2012).…”
mentioning
confidence: 99%
“…This was in accord with the current results in C. japonica infected with A. hydrophila. CTSL is a lysosomal cysteine protease found in rock bream (Whang et al, 2011) and orange spotted groupers (Liang et al, 2012), which acts as a barrier against invading pathogens and is involved in vertebrate immune responses. CTSL acts as a chemical barrier against microbial invasion in the innate immune system (Ellis, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin L (CTSL) is involved in the late stage of Ii degradation, since Ii intermediates, p12 or small leupeptin-induced peptide (SLIP) accumulated due to the deficiency of CTSL [16][17][18][19]. CTSL has also been implicated in regulatory events relating to immunological responses [18,20,21], infectious diseases [22][23][24], cancer [25,26], diabetes [27] and other pathological processes [28][29][30]. Recent studies revealed that CLIK148, a specific inhibitor of CTSL, enhances the development of Th2-type immune responses and leads to exacerbation of leishmaniasis in mice, and CTSL helps contain mycoplasma infection by supporting lymphangiogenesis and cellular immune responses instead of humoral immune responses [28].…”
Section: Introductionmentioning
confidence: 99%